2022
DOI: 10.3389/fnagi.2022.835288
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modifications of the p53 Protein and the Impact in Alzheimer’s Disease: A Review of the Literature

Abstract: Our understanding of Alzheimer’s disease (AD) pathogenesis has developed with several hypotheses over the last 40 years, including the Amyloid and Tau hypotheses. More recently, the p53 protein, well-known as a genome guardian, has gained attention for its potential role in the early evolution of AD. This is due to the central involvement of p53’s in the control of oxidative stress and potential involvement in the Amyloid and Tau pathways. p53 is commonly regulated by post-translational modifications (PTMs), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Posttranslational acetylation is a key mechanism for the regulation of the cellular distribution and degradation of p53 [ 36 ]. It has been shown that the acetylation of p53 influences the cellular distribution of the downstream proteins, including SLC7A11, and ALOX12 [ 10 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Posttranslational acetylation is a key mechanism for the regulation of the cellular distribution and degradation of p53 [ 36 ]. It has been shown that the acetylation of p53 influences the cellular distribution of the downstream proteins, including SLC7A11, and ALOX12 [ 10 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A vital part of the cell's defence systems, the p53 signalling pathway controls cell division, DNA repair, and apoptosis. The p53, is a tumour suppressor protein that is turned on in response to cellular stress [ 95 ]. Its complex signalling cascade coordinates a cell's reaction to threats to its genome and stops damaged cells from multiplying.…”
Section: Functional Implications Of Lncrna Through Hedgehog Signaling...mentioning
confidence: 99%
“…After stimulating these cells with Imp7 and ran to activate the nuclear import mechanism, the presence of mtDNA in the nucleus was observed [101], demonstrating a crosstalk between mitochondrial material and regulatory processes at the nuclear level. Of particular interest in apoptosis, Imp7 inhibition attenuates ribosome biogenesis and activates cell cycle arrest dependent on p53 [102], a protein with a strong pro-apoptotic component, and certain post-translational modifications of this protein may be directly related to AD pathology [103].…”
Section: Regulation Of Apoptosis Vdac and Mitochondrial Traffickingmentioning
confidence: 99%